2017
DOI: 10.1159/000478683
|View full text |Cite
|
Sign up to set email alerts
|

Caveolae Depletion Contributes to Vasorelaxant Effects of Chenodeoxycholic Acid

Abstract: Background/Aims: High concentration of bile acids (BAs) induces hydrophobicity-dependent vasorelaxtant effects with hydrophobic BAs showing greater responses than hydrophilic BAs, of which the underlying mechanisms are still unclear. Caveolae are invaginations on membranes of endothelial cells (ECs) entraping endothelial nitric oxide synthase (eNOS) to prevent its activation, which plays a critical role in regulation of vascular function. The purpose of the present study was to investigate the role of caveolae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Among them, ferulic acid, borneol, and daidzin had strong relaxant effects [Emax (% Phe) > 80%, Table 1 ], which is in accordance with previous findings (Suzuki et al, 2007; Deng et al, 2012; Silva-Filho et al, 2012; Zhao et al, 2014; Zhou et al, 2017; Santos et al, 2019). Magnolol, artemisinin, and chenodeoxycholic acid elicited a moderate relaxation [Emax (% Phe) > 50%, Table 1 ], also consistent with the reports of the previous studies (Teng et al, 1990; Li et al, 2005; Seok et al, 2012; Wang et al, 2017). In addition, our work first reported the vasorelaxant effects of four herbal compounds, liquiritin, ginsenoside Rc, bacopaside I, and ginsenoside Rb2, although the effect is low (Emax (% Phe) < 30%, Table 1 ).…”
Section: Discussionsupporting
confidence: 89%
“…Among them, ferulic acid, borneol, and daidzin had strong relaxant effects [Emax (% Phe) > 80%, Table 1 ], which is in accordance with previous findings (Suzuki et al, 2007; Deng et al, 2012; Silva-Filho et al, 2012; Zhao et al, 2014; Zhou et al, 2017; Santos et al, 2019). Magnolol, artemisinin, and chenodeoxycholic acid elicited a moderate relaxation [Emax (% Phe) > 50%, Table 1 ], also consistent with the reports of the previous studies (Teng et al, 1990; Li et al, 2005; Seok et al, 2012; Wang et al, 2017). In addition, our work first reported the vasorelaxant effects of four herbal compounds, liquiritin, ginsenoside Rc, bacopaside I, and ginsenoside Rb2, although the effect is low (Emax (% Phe) < 30%, Table 1 ).…”
Section: Discussionsupporting
confidence: 89%
“…However, whether ambroxol could improve diabetic vasculopathy remains unclear. CDCA was reported to promote eNOS phosphorylation and NO production that contributes to its vasorelaxant effect (Wang et al, 2017 ). Babu PV reported that genistein can improve diabetes-caused vascular inflammation by suppressing diabetes-induced adhesion of monocytes to endothelial cells and endothelial secretion of adhesion molecules (Babu et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Constant BA stimulation promotes cell apoptosis, which results from oxidative stress with increased reactive oxygen species (ROS) generation [8]. Moreover, BA-damaged hepatocytes produce high levels of inflammatory cytokines, including interleukin (IL)-1β, IL-8, and tumor necrosis factor-α [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%